2019
DOI: 10.21834/e-bpj.v4i12.1912
|View full text |Cite
|
Sign up to set email alerts
|

Stress Coping Mechanism of Children with Learning Disabilities and Effects on Life Satisfaction of Caregivers

Abstract: The caregiver used variety type of coping mechanism to cope with the challenges in raising children with Learning disabilities (Ld). This study aims to identify the correlation between the coping mechanisms used and life satisfaction. The study found that the reframing (p = .018), acquiring social support (p =. 006)and seeking spiritual support (p = .041) have positive correlation while a passive appraisal (p =. 021), has negative correlation with the life satisfaction. Thus, the selected coping mechanisms use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…A study conducted by Nikmat (2008) has found parents with children with ASD have a high prevalence of stress and clinical disturbance in psychological well-being. The authors also found mothers showed a statistically significant impact associated with reduced psychological well-being (Alias, 2019;Nikmat, 2008). This happens due to a global sense of guilt tied to a belief in not doing enough for their children.…”
Section: Establishing the Effectmentioning
confidence: 97%
“…A study conducted by Nikmat (2008) has found parents with children with ASD have a high prevalence of stress and clinical disturbance in psychological well-being. The authors also found mothers showed a statistically significant impact associated with reduced psychological well-being (Alias, 2019;Nikmat, 2008). This happens due to a global sense of guilt tied to a belief in not doing enough for their children.…”
Section: Establishing the Effectmentioning
confidence: 97%